Análise genotóxica do Fipronil® no cérebro de abelhas da espécie Bombus atratus (HYMENOPTERA, BOMBINI) - Provase, Michele (2022)
Fipronil® is a neurotoxic insecticide, effective for control of crop pests. However, there are no data about possible genotoxic effect of sublethal concentrations in the brain of pollinator bees. Therefore, this study aimed sought to analyze the genotoxicity of fipronil® at two concentrations estimated in the field in the brain of foraging workers of Bombus atratus through microelectrophoresis. Workers of B. atratus were collected in the field and transferred to laboratory where they were kept isolately at 26 ºC and 70% relative humidity for 96 hours. Exposure was performed by offering a solution contaminated with fipronil at 2.5 ppb and 3.5 ppb and water as control. Sucrose syrup at 70% was offered to all groups as food ad libitum. After exposure, the workers were crio-anesthezied at 4 ºC and dissected, the removed brain was macerated and centrifuged to isolate the nuclei. The prepared samples were submitted to the Comet Assay technique. Comets were analyzed using an optical microscope, and by the parameters: Damage Index (ID), Damage Frequency (FD%) and Total Damage (DT). Tukey's statistical test was also applied (p<0.05). The results showed that the mean values obtained for ID and FD% showed notable differences between the experimental groups in relation to the control group. However, when analyzing DT through the Tukey test, it was observed that the concentration of 2.5 ppb did not cause significant damage to the DNA of the neural cells of B. atratus (p=0.4434), as observed in the concentration of 3.5 ppb, that induced significant genotoxic effects in the brain of these bees (p=0.0215). Thus, it is concluded that the concentration found in fields of 3.5 ppb is genotoxic to the brain of B. atratus workers.